The Influence of Principal Leadership and Work Commitment on Teacher Professionalism - Puspita, Neni; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine the effect of principal leadership and work commitment to teacher professionalism at SMP Negeri Kayuagung District, Ogan Komering Ilir Regency (OKI). This study uses a quantitative approach. The research sample was 70 state junior high school teachers in Kayuagung District, Ogan Komering Ilir Regency (OKI). Data collection using a questionnaire, data analysis techniques used with simple and multiple regression analysis. The results showed that 1) There was a significant effect of principal leadership on teacher professionalism at SMP Negeri Kayuagung District, Ogan Komering Ilir Regency (OKI), 2) There was a significant effect of work commitment on teacher professionalism in SMP Negeri in Kayuagung District, Ogan Komering Ilir Regency. (OKI), and 3) There is a significant effect of school principal leadership and work commitment to the professionalism of teachers at SMP Negeri Kayuagung Subdistrict, Ogan Komering Ilir Regency (OKI).